DEVELOPMENT OF MEDIA PONARI FOR CIVIC EDUCATION - Nani Widy Astutik Ali; Ratnawan Lukito; Much Yusuf Zen (JOSAR (Journal of Students Academic Research), 2020)
This study to develop learning media, find out the feasibility of the media, and find out the differences in learning outcomes before and after using multimedia-based learning media using Macromedia Flash 8 on the material Harmonization of Human Rights and Obligations in the Pancasila Perspective PKn subjects in class XI 1 Kademangan Public High School . Determination of the feasibility level of multimedia-based learning media based on expert validation tests and small-scale trials was then applied to the sample class. Data collection techniques using questionnaires, and tests. Thus can help the effective learning process to improve student learning outcomes, by looking at the results of the average and completeness of student learning.